Pelatihan Website Knowledge Sharing System sebagai Media Berbagi Pengetahuan Kerajinan Tangan bagi Nasyiatul ‘Aisyiyah - Debby Ummul Hidayah; Nailis Syafi’ah; Ikhsan Setiawan (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
This community service activity has been successfully carried out which is located in Bustanul 'Aisyiyah, Rabak Village, Kalimanah District, Purbalingga Regency. This community service activity is in the form of training on the use of the knowledge sharing system (KSS) website and at the same time the practice of making handicrafts from wool yarn. The tools and materials used in making handicrafts include wool, paper, scissors, wire, and green tape. Meanwhile, training in using the KSS website requires a device such as a mobile and an internet connection. The purpose of this community service activity is to increase knowledge in the use of information technology, namely in the form of a knowledge sharing system website as a medium for sharing handicrafts. The method of implementation is by lecturing and practicing directly using the KSS website and making handicrafts. The outputs of this service activity are (1) Members of Nasyiatul 'Aisyiyah Desa Rabak have knowledge of the use of information technology to share knowledge and hone skills as pillars in the foundation of entrepreneurial TOT; (2) Members of Nasyiatul 'Aisyiyah Rabak can share knowledge about handicrafts through the KSS website.